Start-Up Capital and Women's Entrepreneurship: Evidence from Swaziland - Zuzana Brixiova; Thierry Kangoye (Institute for the Study of Labor (IZA), 2016)
This paper examines gender differences in entrepreneurial performance and their links with start-up capital utilizing a search model and empirical analysis of survey of entrepreneurs from Swaziland. The results show that entrepreneurs of both genders with higher start-up capital record better sales performance than those with smaller amounts of capital. For women entrepreneurs, formal finance sources of start-up capital are also associated with higher sales. However, as in other developing countries, women entrepreneurs in Swaziland have smaller start-up capital and are less likely to fund it from formal sources than men. Among women entrepreneurs, those with college education and confident in their skills tend to start their firms with higher amounts of capital. Professional support also matters, as women with such support are more likely to fund their start-up capital from the formal financial sector.
Keywords: L53; O12; C61; 330; women's entrepreneurship; start-up capital; search model; multivariate analysis